Strengthening women’s empowerment, climate resilience, and nutrition along the goat value chain in Senegal: A qualitative study - Kane, Papa Abdoulaye; Barry, Mamadou Bobo; Eissler, Sarah; Tall, Thiané; Camara, Astou Diao; Sall, Moussa; Fass, Simone; Bryan, Elizabeth; Ringler, Claudia (International Food Policy Research Institute, 2024)
Goats are an important source of income, nutrition and resilience in Senegal. This study assesses opportunities to strengthen women’s agency, increase resilience to climate change, and improve nutrition along the various stages of goat value chains from the acquisition of feed resources and other inputs to processing, marketing and consumption of various goat products. The qualitative study finds that even though goats are more climate resilient than other livestock, climate change impacts on goat production and productivity are increasingly felt, particularly through impacts on feed resources. The study identified opportunities to strengthen women’s roles along the goat value chain, particularly in goat production and, to a lesser extent, in processing of goat products. Women and their families also benefit from the consumption of goat milk and women have some degree of control over income from the sale of goat products. Strengthening women’s agency in these nutrient-rich and relatively climate-resilient value chains will require improving their access to land resources and better animal feeds, supporting women’s groups and building women’s capacity for processing and marketing goat products, improving access to electricity for cold storage of goat products, and raising awareness regarding the nutritional benefits of goat products, especially for women and children.